Desulfovibrio diazotrophicus sp. nov., a sulfate‐reducing bacterium from the human gut capable of nitrogen fixation. (14th May 2021) - Sayavedra, Lizbeth; Li, Tianqi; Bueno Batista, Marcelo; Seah, Brandon K. B.; Booth, Catherine; Zhai, Qixiao; Chen, Wei; Narbad, Arjan
Summary: Sulfate‐reducing bacteria (SRB) are widespread in human guts, yet their expansion has been linked to colonic diseases. We report the isolation, sequencing and physiological characterization of strain QI0027 T, a novel SRB species belonging to the class Desulfovibrionia . Metagenomic sequencing of stool samples from 45 Chinese individuals, and comparison with 1690 Desulfovibrionaceae metagenome‐assembled genomes recovered from humans of diverse geographic locations, revealed the presence of QI0027 T in 22 further individuals. QI0027 T encoded nitrogen fixation genes and based on the acetylene reduction assay, actively fixed nitrogen. Transcriptomics revealed that QI0027 T overexpressed 42 genes in nitrogen‐limiting conditions compared to cultures supplemented with ammonia, including genes encoding nitrogenases, a urea uptake system and the urease complex. Reanalyses of 835 public stool metatranscriptomes showed that nitrogenase genes from Desulfovibrio bacteria were expressed in six samples suggesting that nitrogen fixation might be active in the gut environment. Although frequently thought of as a nutrient‐rich environment, nitrogen fixation can occur in the human gut. Animals are often nitrogen limited and have evolved diverse strategies to capture biologically active nitrogen, ranging from amino acid transporters to stable associations with beneficial microbes that provide fixed nitrogen. QI0027 T is the first Desulfovibrio human isolate for which nitrogen fixation has been demonstrated, suggesting that some sulfate‐reducing bacteria could also play a role in the availability of nitrogen in the gut.